2022
DOI: 10.1002/jat.4334
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of chlorpyrifos and cyfluthrin on neurobehavior and neurotransmitter levels in larval zebrafish

Abstract: Chlorpyrifos and cyfluthrin are insecticides commonly used in agriculture. The mixed residues of chlorpyrifos and cyfluthrin in the aquatic environment may have combined effects on nontarget species. Therefore, studying the combined toxic effects and mechanisms of pesticide mixtures is of great significance to environmental risk assessment. To evaluate the risk of combined exposure, we examined the effects of both compounds, separately and together, on motor activity, acetylcholinesterase (AChE) activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The Dark 2 epoch allowed for the analysis of photomotor behavioral responses induced by the switching from light to dark, whereas the Dark 3 and Dark 4 epochs that immediately followed without a change in light stimulation allowed us to observe the effects of chemical exposures on the typical habituation of the motor response to continued dark. Significant changes in swimming behavior compared to vehicle control fish suggest nervous system dysfunction. …”
Section: Resultsmentioning
confidence: 99%
“…The Dark 2 epoch allowed for the analysis of photomotor behavioral responses induced by the switching from light to dark, whereas the Dark 3 and Dark 4 epochs that immediately followed without a change in light stimulation allowed us to observe the effects of chemical exposures on the typical habituation of the motor response to continued dark. Significant changes in swimming behavior compared to vehicle control fish suggest nervous system dysfunction. …”
Section: Resultsmentioning
confidence: 99%
“…Chemicals could cause neurotoxicity by binding and inducing phosphorylation on the serine hydroxyl group at the active site-esterification of AChE during embryonic development. 81 The inhibition of AChE could affect the acetylcholine level and cholinergic neurotransmission, which further results in AChE-mediated neurotransmission impairment abnormalities such as psychomotor defects, respiratory depression, thigmotaxis, etc. 82 A decreased heart rate could reduce oxygen concentration and affect the flow in the circulatory system which eventually causes disruption of cholinergic signalling in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…After the test, the rats were anaesthetized and sacrificed for follow-up experiments(Figure 1). [10,11]. Therefore, in this study, a rat model of nerve injury induced via Cy e established to explore the relationship between Cy exposure and neurobeh aptic plasticity, the inflammatory response and adenosine A2AR expression in damaging effect of Cy exposure on the nervous system of Wistar rats.…”
Section: Animalsmentioning
confidence: 99%
“…After entering the body, Cy can pass through the blood-brain barrier, accumulate in brain tissue and damage the human nervous system Toxics 2023, 11, 999 2 of 21 to varying degrees [9]. Some epidemiological investigations have also shown that longterm exposure to Cy and other pyrethroid pesticides can lead to a variety of nervous system disorders and even the precursor symptoms of neurodegenerative diseases [10,11]. Therefore, in this study, a rat model of nerve injury induced via Cy exposure was established to explore the relationship between Cy exposure and neurobehaviour, synaptic plasticity, the inflammatory response and adenosine A 2A R expression in rats and the damaging effect of Cy exposure on the nervous system of Wistar rats.…”
Section: Introductionmentioning
confidence: 99%